2020
DOI: 10.3390/ijms21207575
|View full text |Cite
|
Sign up to set email alerts
|

Microbes as Medicines: Harnessing the Power of Bacteria in Advancing Cancer Treatment

Abstract: Conventional anti-cancer therapy involves the use of chemical chemotherapeutics and radiation and are often non-specific in action. The development of drug resistance and the inability of the drug to penetrate the tumor cells has been a major pitfall in current treatment. This has led to the investigation of alternative anti-tumor therapeutics possessing greater specificity and efficacy. There is a significant interest in exploring the use of microbes as potential anti-cancer medicines. The inherent tropism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 149 publications
0
23
0
Order By: Relevance
“…Although bacteria were traditionally regarded as carcinogenic, there is now available evidence for their anticancer properties. The role of the microbiome in cancer treatment was proposed as early as 1867, when it was reported that infection with Streptococcus pyogenes caused cancer remission in a patient ( Sawant et al, 2020 ). Bacteria exert anticancer effects via multiple mechanisms including (i) colonizing tumors, (ii) releasing substances, (iii) suppressing nutrients required for tumor metabolism and proliferation, (iv) serving as a vehicle for anticancer drugs delivery, (v) forming biofilms, and (vi) enhancing host immunity ( Soleimanpour et al, 2020 ; Yaghoubi et al, 2020 ).…”
Section: Role Of Bacteria In the Treatment Of Gcmentioning
confidence: 99%
“…Although bacteria were traditionally regarded as carcinogenic, there is now available evidence for their anticancer properties. The role of the microbiome in cancer treatment was proposed as early as 1867, when it was reported that infection with Streptococcus pyogenes caused cancer remission in a patient ( Sawant et al, 2020 ). Bacteria exert anticancer effects via multiple mechanisms including (i) colonizing tumors, (ii) releasing substances, (iii) suppressing nutrients required for tumor metabolism and proliferation, (iv) serving as a vehicle for anticancer drugs delivery, (v) forming biofilms, and (vi) enhancing host immunity ( Soleimanpour et al, 2020 ; Yaghoubi et al, 2020 ).…”
Section: Role Of Bacteria In the Treatment Of Gcmentioning
confidence: 99%
“…It was demonstrated different mechanisms of action for individual compounds, from induction of replicative stress to disbalance of cation homeostasis to inhibition of bacterial attachment to the surface. Study demonstrates the potential of drug repurposing for the prevention of bacterial biofilm formation and suggests that also for other bacteria, the activity spectrum of antibiofilm compounds is likely to be broad [42].…”
Section: Resultsmentioning
confidence: 95%
“…For example, inflammation is an important hallmark of cancer, and the presence of immune cells known as tumor associated macrophages (TAM) is often conducive of tumor growth, metastases and poor outcomes (Gharib et al, 2019;Laoui et al, 2011). TAMs are broadly M2 polarized, and IL-10, IL-12p40 and G-CSF all have been shown to play important roles in impacting the tumor microenvironment through regulation of TAMs (Biswas et al, 2006;Kanemaru et al, 2017;Karagiannidis et al, 2020;Laoui et al, 2011) which could be targeted by the EES in cancer bacteriotherapy (Sawant et al, 2020;Yaghoubi et al, 2019Yaghoubi et al, , 2020bYaghoubi et al, , 2020aZhang et al, 2020). Arthritis represents the other side of immune polarization where homeostasis is driven to a proinflammatory condition (Georgopoulos et al, 1996;Henderson and Pettipher, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Precedence exists for using bacteria to impact mammalian cell physiology for therapeutic approaches, known as bacteriotherapy, and advances in this field support the development of EES for cellular control. Bacille Calmette-Guerin (BCG, the Mycobacterium bovis strain used as a tuberculosis vaccine) bacteriotherapy has become standard of care for bladder cancer treatment, and many other clinical applications for bacteriotherapy are being devised and tested, including for the treatment of other cancers (Laliani et al, 2020;Sawant et al, 2020;Sedighi et al, 2019;Yaghoubi et al, 2019Yaghoubi et al, , 2020aZhang et al, 2020). Bacterial systems, including EES, represent a potentially powerful means of exploiting prokaryotic versatility for therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%